Interrater agreement of contouring of the neurovascular bundles and internal pudendal arteries in neurovascular-sparing magnetic resonance-guided radiotherapy for localized prostate cancer. (January 2022) - Teunissen, F.R.; Wortel, R.C.; Wessels, F.J.; Claes, A.; van de Pol, S.M.G.; Rasing, M.J.A.; Meijer, R.P.; van Melick, H.H.E.; de Boer, J.C.J.; Verkooijen, H.M.; van der Voort van Zyp, J.R.N.
Highlights: Interrater DSC of the NVB was 0.60 and 0.61 for the left and right side respectively. Interrater DSC of the IPA was 0.59 for the left and right side. Agreement was best for the inferior half (i.e. prostate apex to midgland) of the NVB. Agreement improved with MRI optimization and rater training. Abstract: Background and purpose: Radiation damage to neural and vascular tissue, such as the neurovascular bundles (NVBs) and internal pudendal arteries (IPAs), during radiotherapy for prostate cancer (PCa) may cause erectile dysfunction. Neurovascular-sparing magnetic resonance-guided adaptive radiotherapy (MRgRT) aims to preserve erectile function after treatment. However, the NVBs and IPAs are not routinely contoured in current radiotherapy practice. Before neurovascular-sparing MRgRT for PCa can be implemented, the interrater agreement of the contouring of the NVBs and IPAs on pre-treatment MRI needs to be assessed. Materials and methods: Four radiation oncologists independently contoured the prostate, NVB, and IPA in an unselected consecutive series of 15 PCa patients, on pre-treatment MRI. Dice similarity coefficients (DSCs) for pairwise interrater agreement of contours were calculated. Additionally, the DCS of a subset of the inferior half of the NVB contours (i.e. approximately prostate midgland to apex level) was calculated. Results: Median overall interrater DSC for the left and right NVB was 0.60 (IQR: 0.54 – 0.68) and 0.61 (IQR: 0.53 – 0.69) respectively and for the left and right IPA 0.59 (IQR: 0.53 – 0.64) and 0.59 (IQR: 0.52 – 0.64) respectively. Median overall interrater DSC for the inferior half of the left NVB was 0.67 (IQR: 0.58 – 0.74) and 0.67 (IQR: 0.61 – 0.71) for the right NVB. Conclusion: We found that the interrater agreement for the contouring of the NVB and IPA improved with enhancement of the MRI sequence as well as further training of the raters. The agreement was best in the subset of the inferior half of the NVB, where a good agreement is clinically most relevant for neurovascular-sparing MRgRT for PCa.